Pro-poor growth through export sector support: What works where and why? - Henrik Nielsen; Peter Gibbon (Danish Institute for International Studies (DIIS), 2011)
This report reviews international experiences with pro-poor development assistance to export sectors. Such support has become more common in the last 15 years, following the emergence of widespread consensus amongst policymakers that export growth can be a key poverty reduction mechanism. Policymakers also agree that some types of export growth are more (potentially) pro-poor than others, especially but not only in their employment effects. The initiatives designed to respond to this challenge are the focus of this report.
Keywords: 300